KEMAMPUAN MENULIS TEKS EDITORIAL SISWA KELAS XII SEMESTER I SMA NEGERI 1 SUNGAI LASI KECAMATAN IX KOTO SUNGAI LASI KABUPATEN SOLOK TAHUN PELAJARAN 2023/2024 - SILVITA, DEVI; Halid, Elan; Putri, Mega (Program Studi Pendidikan Bahasa Indonesia, , Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mahaputra Muhammad Yamin, 2024)
This research aims to describe the ability to write editorial texts for students in class The population of this study were students of class The research sampling technique was carried out using a random sampling technique, namely by taking the entire population as a sample if the population was less than 100. The data collection technique in this research was a performance test. Data analysis techniques include reading, correcting and scoring student test results, converting raw scores into grades, classifying student scores on a scale of 10, making a histogram, and summarizing the results in the form of a thesis. The results of research on the ability to write editorial texts based on linguistic structures and rules, the average score of students' ability to write editorial texts based on the structure of the issue introduction section is at perfect qualifications with an average score of 100. The students' ability to write editorial texts based on the structure of the argumentation section is at excellent qualifications with an average score of 100. Students' ability to write editorial texts based on the structure of the conclusion and recommendation sections is in very good qualifications with an average score of 90.66. Students' ability to write editorial texts based on linguistic rules for parts of popular words is at perfect qualifications with an average score of 100. Students' ability to write editorial texts based on linguistic rules for parts of time, place and events is at perfect qualifications with an average score of 99. 56. Students' ability to write editorial texts based on linguistic rules for persuasive sentences is more than adequate with an average score of 66.23. Students' ability to write editorial texts based on the linguistic rules of the conflicting conjunction section is at almost sufficient qualifications with an average score of 52.89. The students' ability to write editorial texts based on the linguistic rules of our pronoun section is at a sufficient qualification with an average score of 65.33. Based on the qualifications above, it can be concluded that the students' ability to write editorial texts in class XII Semester 1 of SMA Negeri 1 IX Koto Sungai Lasi, Solok Regency Academic Year 2023/2024 is in good qualifications (BK) with a mastery level of 76-85% with an average score of 84.77.